Avaliação de silagens de capim elefante aditivadas com farelo de milho e inoculante da microbiota autóctone - Bezerra, Higor Fábio Carvalho (2013)
Two experiments were conducted with the objective of evaluating the elephant grass silages added with corn bran and inoculation of autochthonous microbiota , being held at the Center for Agricultural Sciences , Federal University of Paraiba (UFPB) in Areia - PB. The first experiment aimed to evaluate the fermentation characteristics, the recovery of dry matter and chemical composition of elephant grass silage added with corn bran and inoculation of autochthonous microbiota. To evaluate the fermentation characteristics as well as other features we used a scheme 4 x 2 (four levels of corn bran x with and without inoculation) in a completely randomized design with five replications. The peak development of populations of lactic acid bacteria was observed when it was not employed any additive (9.61 log CFU/g). For values of lactic acid was observed significant effect (P <0.05) for both inoculant as corn bran, presenting a quadratic relation, decreasing the concentration of lactic acid from the use of 10 dag/kg corn bran. The addition of the inoculant increased the silages dry matter recovery in the absence of corn bran. However there was no significant difference (P<0.05) in the addition of inoculum in the presence of corn bran. The values of effluent losses declined linearly with increasing levels of corn bran. Gas losses were higher when it was added corn bran. The contents of dry matter, organic matter, crude protein, ether extract, total carbohydrates and non-fiber carbohydrates, linear reduction (P<0.05), depending on the levels of corn bran. The neutral detergent fiber obtained a linear decrease (P <0.05). Significant effects (P <0.05) only for the inoculant organic matter and carbohydrates, with increased levels using the same. The inoculation of autochthonous microbiota enhances the fermentation characteristics of elephant grass silage only in the absence of corn bran, and the corn bran provides improvement in fermentation characteristics and composition of silage independent of the inoculant, being indicated for inclusion of 20 dag / kg of corn bran. The second experiment aimed to evaluate the degradation potential of silages with corn bran and inoculation of autochthonous microbiota in fistulated cattle. For degradability evaluation we used up a block design with split plot in which three animals represented the blocks; silages were the xvi main plots, and seven hours of food ruminal incubation, the subplots. With the addition of corn bran there was an increase in the fraction of the silages, and so treatments with 20 dag/kg of corn bran fraction resulted in higher values of the dry matter, 31.49 and 29.02%, for treatments with and without inoculant, respectively. The insoluble potentially degradable fraction (B) of dry matter was higher in silages with 20 dag/kg of corn bran. In neutral detergent fiber, higher values of Bp were observed in the silage without corn bran, 56.52 and 57.19%, respectively, in the silages with and without inoculation of autochthonous microbiota. The addition of corn bran of elephant silage improves dry matter degradability of silages and decreases of neutral detergent fiber.